Pengaruh Leverage, Struktur Modal Dan Kepemilikan Institusional Terhadap Kinerja Keuangan Perusahaan (Studi Pada Perusahaan Rokok yang Tedaftar di BEI Periode 2001-2015) - Andika, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Financial performance in a company describes the ability of a company to manage its capital to generate profit for the welfare of investors. Financial performance in this study is measured by the profitability ratios of Earning Per Share. This study aims to determine the effect of leverage as measured by Debt To Asset Ratio, capital structure as measured by Longterm Debt to Equity Ratio and institutional ownership to the company's financial performance as measured by Earning Per Share. The model used to analyze the effect of these variables is multiple linear regression using SPSS that meets the criteria of classical assumption test. The sample used in this study amounts to 2 companies that meet the criteria. The results of this study indicate that the leverage measured by Debt to Asset Ratio has no significant effect on Earning Per Share, the capital structure measured by Longterm Debt to Equity Ratio has significant effect on Earning Per Share and institutional ownership significantly influence EPS. The dominant test results show that the variable Longterm Debt to Equity Ratio dominant influence on financial performance as measured by Earning Per Share.KeywordsÂ : Leverage , Capital structure, Debt to Asset Ratio (DAR), Longterm Debt to Equity Ratio (LDER), Institutional Ownership, Financial Performance, Earning Per Share (EPS)